2019
DOI: 10.1112/plms.12241
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on layer potentials with rough inputs for higher order elliptic equations

Abstract: In this paper, we establish square‐function estimates on the double and single layer potentials with rough inputs for divergence form elliptic operators, of arbitrary even order 2m, with variable t‐independent coefficients in the upper half‐space.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…See [24]. We remark that this definition coincides with the definition of S Lġ involving the Newton potential given in [19,20]. In [23] we showed that S L extends by density to an operator defined on all of L p (R n ) for p sufficiently close to 2 and that satisfies the bound (1.19).…”
Section: Function Spaces and Dirichlet Boundary Valuesmentioning
confidence: 59%
See 4 more Smart Citations
“…See [24]. We remark that this definition coincides with the definition of S Lġ involving the Newton potential given in [19,20]. In [23] we showed that S L extends by density to an operator defined on all of L p (R n ) for p sufficiently close to 2 and that satisfies the bound (1.19).…”
Section: Function Spaces and Dirichlet Boundary Valuesmentioning
confidence: 59%
“…See, for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. t-independent coefficients in the higher order case have received much more limited study; Hofmann and Mayboroda together with the author of the present paper have begun their study in [19][20][21][22][23]. Specifically, in [22], we established the following result.…”
mentioning
confidence: 74%
See 3 more Smart Citations